Revisiting ovarian hyper stimulation syndrome: Towards OHSS free clinic - Manish Banker; Juan A Garcia-Velasco (Wolters Kluwer Medknow Publications, 2015)
A rapid development and application of assisted reproductive technologies (ARTs) and ovulation-induction drugs may lead to ovarian hyper stimulation syndrome (OHSS). Young age, low body mass index (BMI), polycystic ovarian syndrome (PCOS), previous OHSS, high follicle count, and elevated serum estradiol (E2) are the certain factors that predispose women to OHSS. Many strategies have been used to reduce or avoid OHSS. Use of human chorionic gonadotropin (hCG) increases ovarian vascular permeability and is responsible for activating the vascular endothelial growth factors (VEGF) pathway and thus the entire cascade, leading to symptomatic OHSS. Gonadotropin-releasing hormone (GnRH) agonists are used as a replacement for hCG for final oocyte maturation in antagonist cycles. Reducing or eliminating the use of hCG and use of GnRH agonist triggered GnRH antagonist cycles and cryopreservation of oocytes or embryos is the most promising approach in making OHSS free clinic a reality.